Desenvolvimento de arcabouço descelularizado para uso em bioengenharia tecidual esplênica - Zanardo, Tadeu Ériton Caliman (2020)
The spleen has already been considered a non-essential organ for life. However, its importance is increasingly clear, given the serious disorders caused by its absence or dysfunction, such as increased susceptibility to infections, thromboembolism and cancer. In addition, it is known that its non-functionality may lead to patients already afflicted with serious diseases such as HIV, myeloma and leukemia to have a higher risk of infection and death. Therefore, we used the technique of decellularization to obtain a viable splenic scaffold for recellularization and subsequent transplantation to the host. In our study, we demonstrated that the scaffold created after the decellularization process shows great removal of the DNA content and residual SDS, which are essential and necessary to avoid immunogenic responses and failures after transplantation to the host. In addition, there were preservation of the major components of matrissome, such as collagens, glycoproteins and proteoglycans. In the same way, we observed maintenance of important structural components such as white pulp, marginal zone and red pulp, in addition to small, medium and large caliber blood vessels. The scaffold developed by us was subsequently recellularized with stromal cells from the spleen of neonate rats, where we verified the ability of adhesion, proliferation, viability and survival of cells in contact with the scaffold. Therefore, the splenic scaffold proves to be very useful for studies that intend to use it for the recovery of splenic function or even as a support for studies that intend to study changes in the splenic extracellular matrix caused by diseases